Nonlinear Finite Element Analysis of I-Steel Beam with Sinusoidal Web - Abd Matooq, Jawad; Khalaf, Majed A.; Al Menhosh, Adel A.; Almayah, Abdulamir A.; Majeed, Fareed H. (Salehan Institute of Higher Education, 2025)
For structural models, existing research frequently uses deterministic numerical analysis. Test findings, however, constantly point out uncertainties, especially about variables like the imposed load's amplitude, geometrical dimensions, material unpredictability, and inadequate experiential data. In response, scholars have focused more on probabilistic design models, realizing their importance for precisely forecasting structural performance. This research aims to incorporate reliability-based analysis into the numerical modeling of steel beams with sinusoidal webs. A steel welded plate beam with an I-section and a sinusoidal web has been taken into consideration in this study. The web height is 750 mm, the web thickness is 2.0 mm, the flange width is 300 mm, and the flange thickness is 5.0 mm. The beam's length, l = 1000 mm, has two 10.0 mm thick stiffeners positioned beneath the applied load to stop the flange from failing locally as a result of load concentration and end plate supports that are 5 mm thick. The commercial software application ANSYS ver. 2019 R3 has been used to perform a nonlinear finite element analysis in order to examine the failure modes and load capacities. In the first stage of this study, the changing of the amplitude/period ratio, A/P, was taken into consideration to examine the failure capacity loads and deformed shapes to optimize the amplitude/period ratio. In the second stage, the optimum amplitude/period ratio, A/P, was taken, and changing the period/span ratios, P/L, made the best use of the period/span ratios by examining the failure capacity loads and deformed forms. Doi: 10.28991/CEJ-2025-011-03-08 Full Text: PDF